2018
DOI: 10.17719/jisr.2018.2720
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Hi̇zmet Bölümü Öğrenci̇leri̇ni̇n Yaşlilik Ve Yaşlanmaya İli̇şki̇n Tutumlarinin Beli̇rlenmesi̇

Abstract: Öz Araştırma, sosyal hizmet bölümünde öğrenim gören öğrencilerin yaşlılık ve yaşlanmaya ilişkin tutumlarının bireysel özelliklerine göre karşılaştırılması amacıyla yapılmıştır. Tanımlayıcı tipte bir araştırmadır. Çalışma grubundan veriler, araştırmacılar tarafından hazırlanan demografik sorulara ek olarak Otrar (2016) tarafından geliştirilen "Yaşlılık ve Yaşlanmaya İlişkin Tutum Ölçeği" ile toplanmıştır. Ölçek 18 yaş üzeri bireylerin yaşlanmaya ve yaşlılığa yönelik gözlem ve izlenimlerini belirlemek amacıyla h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…97,98 Various studies have been conducted in Turkey about the attitudes of healthcare workers and social workers toward the elderly in the context of healthcare services. 18,[99][100][101][102][103] Uğurlu et al 104 determined that the attitudes of healthcare workers toward the elderly are generally positive. 104 Other research has revealed that doctors and nurses have positive attitudes toward the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…97,98 Various studies have been conducted in Turkey about the attitudes of healthcare workers and social workers toward the elderly in the context of healthcare services. 18,[99][100][101][102][103] Uğurlu et al 104 determined that the attitudes of healthcare workers toward the elderly are generally positive. 104 Other research has revealed that doctors and nurses have positive attitudes toward the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Dünyada ve ülkemizde yaşlı nüfusun hızla artmasıyla birlikte yaşanan sosyo-ekonomik sorunlar, çok sayıda araştırmacıyı bu konuda araştırma yapmaya yöneltmiştir (Şahin & Demirel, 2018(Şahin & Demirel, , s.1118…”
Section: Tartişma Ve Sonuçunclassified